Assessing an autistic student's reading comprehension through task-based activities: self-study through narrative inquiry - Kristiyantini Kristiyantini; Amalul Umam (Journal of English Language Learning, 2021)
The understanding reading text is essential for every student. Without knowing the reading content, students will not get information or lessons from the text they read, so it is necessary to assess their reading ability TBLT in the reading learning process. For this reason, researchers conducted research using a qualitative approach by applying the self-study method on narrative inquiry. For this reason, researchers exported their experiences when implementing TBLT to assess an autistic student named Dimas. The learning implementation is divided into three stages. It is reading tasks, drawing tasks, and retelling tasks. All of the tasks are interrelated. The researchers hoped that this research could become a reference for teachers to apply assessment with TBLT and contribute to the development of education globally and comprehensively, especially in Indonesia. The data used in this study are documentation, journal diary, field notes. The validity is done by linking the data from the documentation, journal diary, field notes, and for data analysis, the researcher connects the data with previous theories.